2017
DOI: 10.29244/jhi.8.1.39-47
|View full text |Cite
|
Sign up to set email alerts
|

Pewarisan Sifat Ketahanan Cabai terhadap Infestasi Aphis gossypii Glover (Hemiptera: Aphididae)

Abstract: Aphis gossypii Glover is one of the major pests of chili pepper and can cause damage up to ABSTRAKKutudaun Aphis gossypii Glover adalah salah satu hama pengganggu penting dalam produksi tanaman cabai. Saat populasi kutudaun tidak terkendali dapat menyebabkan kerusakan tanaman cabai hingga 65%. Tujuan penelitian ini adalah mempelajari kendali genetik pewarisan sifat ketahanan cabai (Capsicum annuum L.) terhadap infestasi A. gossypii. Set populasi enam generasi (P 1 , P 2 , F 1 , F 2 , BC P1 , BC P2 ) dibentuk d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Note: Numbers Followed by the Same Letter in the Same Column Are Not Significantly Different Based on the Honestly Significant Difference Test (BNJ) level 0.05 [2]stated that the character of a plant that is taller and does not touch the ground can reduce water splashing from the soil to the fruit which is one source of disease infection. [10]stated that the fruit from higher plants does not touch the ground so that it can reduce water splashing from the soil to the fruit which is one source of fungal infection.…”
Section: Plant Height and Dichotomousheightmentioning
confidence: 99%
See 1 more Smart Citation
“…Note: Numbers Followed by the Same Letter in the Same Column Are Not Significantly Different Based on the Honestly Significant Difference Test (BNJ) level 0.05 [2]stated that the character of a plant that is taller and does not touch the ground can reduce water splashing from the soil to the fruit which is one source of disease infection. [10]stated that the fruit from higher plants does not touch the ground so that it can reduce water splashing from the soil to the fruit which is one source of fungal infection.…”
Section: Plant Height and Dichotomousheightmentioning
confidence: 99%
“…CKD061 was able to increase viability and seed vigour of local upland rice cultivars. The treatment showed that the seed vigour index increased by 133% in the Waburi-buri cultivar and 127% in the Daindo Mornene cultivar when compared to the control [9] Increased productivity of chili can be done by improving genetic potential through the formation of hybrid varieties and the use of superior varieties [10]The use of bio-priming on local varieties of Aceh will increase germination vigour, growth and will maximize yield potential and resistance to Begomovirus.…”
Section: Introductionmentioning
confidence: 99%
“…Stadia kutu daun yang diinfestasikan adalah imago tak bersayap sebanyak 5 ekor per tanaman. Bibit cabai rawit merah yang digunakan berumur 5 minggu setelah semai (MSS) atau telah memiliki 4-6 helai daun (Daryanto et al, 2017b), selanjutnya tanaman ditutup sungkup plastik berdiameter dan tinggi 30 cm serta tertutup kain dengan kerapatan 50 mesh selama 4 minggu.…”
Section: Uji Ketahanan Terhadap Kutu Daun a Gossypiiunclassified
“…Diallel cross analysis with Hayman's approach has widespread use in studying the genetic basis of various traits in chili, including genetic parameters' evaluation in early generations for begomovirus resistance and agronomic features (Ganefianti et al, 2015), host plant resistance in chili pepper (Daryanto et al, 2017), yield and spiciness components (Sahid et al, 2021), bacterial wilt disease resistance in chili (Dhillon et al, 2022), evaluation of secondary metabolites in chili (Syukur et al, 2023), and rice genotypes for yield-related traits (Riyanto et al, 2023).…”
Section: Introductionmentioning
confidence: 99%